Assessing Visual Preferences of the Local Public for Environmental Mitigation Measures of Hydropower Impacts—Does Point-of-View Location Make a Difference? - Berit Junker-Köhler (MDPI AG, 2021)
Hydropower is a highly appreciated climate-friendly source of energy production. However, it has non-negligible negative impacts on the environment and landscape aesthetics where the energy is produced, affecting the recreational interests of the public using the respective local river spaces. The preferences of the local public are increasingly assessed and involved in the planning of mitigation measures for impacted rivers. Aesthetic assessment methods using a common user perspective, i.e., an “on-the-ground” perspective, could potentially be improved by using an aerial perspective facilitated by modern drone technology. Studies on the compatibility of these two perspectives of assessment in terms of public preference elicitation are lacking so far. In river Nea, Norway, we conducted a quantitative analysis of the visual preferences of the local public for different environmental mitigation measures related to weirs, minimum flow, and recreational infrastructure using both perspectives. The results indicate that there exist significant differences in the preferences for scenarios based on the two different visual perspectives, and that a compatibility between them cannot be assumed and therefore requires further investigation. Finally, based on our study setup and previous experience, we outline and propose a standardized procedure for the visualization of mitigation measures as an input to environmental design projects where public perception is incorporated.